The peanuts movie - Martino, Steve, 1959-; Schulz, Craig; Schulz, Bryan; Uliano, Cornelius, 1985-; Schnapp, Noah; Melendez, Bill; Miller, Hadley Belle; Andrews, Troy; Bloom, Rebecca; Bredikhina, Anastasia; Garfin, Alex; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, California : Twentieth Century Fox Home Entertainment, 2016)
Charlie Brown, Snoopy, Lucy, Linus, and the rest of the Peanuts gang make their big-screen debut in state-of-the-art 3D animation. Charlie Brown embarks upon an epic and heroic quest, while his best pal, the lovable beagle Snoopy, takes to the skies to pursue his arch-nemesis, the Red Baron.
Originally released as a motion picture in 2015.
Special features: 6 Snoopy snippets; "Better when I'm dancin'" Megan Trainor music & lyric videos; learn to draw Snoopy, Woodstock and Charlie Brown; Get down with Snoopy and Woodstock music video; behind the scenes of "Better when I'm dancin'"; Snoopy's playlist.
Voices of: Noah Schnapp, Bill Melendez, Hadley Belle Miller, Trombone Shorty, Rebecca Bloom, Anastasia Bredikhina, Alexander Garfin.
MPAA rating: G.
DVD, widescreen (1.85:1); Dolby digital 5.1 (English), Dolby digital 2.0 (Spanish, French), English descriptive audio 5.1; NTSC, region 1, dual layer.
English, Spanish or French dialogue; Spanish or French subtitles; English subtitles for the deaf and hard of hearing; described video.
Keywords: Brown, Charlie -- (Fictitious character) -- Juvenile drama; Snoopy (Fictitious character) -- Juvenile drama; Friendship -- Juvenile drama; Animated films; Children's films; Feature films